Pulmonary artery aneurysm caused by infective endarteritis attributed to patent ductus arteriosus in children: a case report and literature review - Wu, Pengpeng; Zheng, Chao; Zhang, Feng; Wang, Pingsheng; Zhang, Haiyong; Chen, Gang (Frontiers in Pediatrics, 2023)
We report a case of a ten-year-old male patient with pulmonary artery aneurysm caused by infective endarteritis of the pulmonary artery due to patent ductus arteriosus. He was found to have patent ductus arteriosus at the age of 2 years, but he was not treated due to the absence of symptoms and normal physical development. He sought medical attention for fever and cough 3 months ago. Echocardiography showed pulmonary artery aneurysm, intrapulmonary artery bulge, patent ductus arteriosus and pericardial effusion. Contrast-enhanced CT showed pulmonary artery aneurysm, patent ductus arteriosus and slight compression of the left main bronchus. Surgery was performed to reconstruct the main pulmonary trunk and repair the ductus arteriosus. The surgical outcomes are satisfactory.